Collective fear and social representations of COVID-19. The role of the original 'reasons' for the fear object (Miedo colectivo y representaciones sociales de la COVID-19. El rol de las 'razones' originales para el objeto de miedo). Issue 2 (4th May 2022) - Tavani, Jean-Louis; Delouvée, Sylvain; Rateau, Patrick
ABSTRACT: Based on a taxonomy of collective fears, the objective of the study ( N = 1, 144) was to analyse how the original reasons attributed to an object of fear play a role in collective angst and to study how these attributions are linked to differentiated social representations of the object. The results show that the underlying reasons (human vs. non-human; intentional vs. unintentional) organize the socio-representational field of the coronavirus. Moreover, the fact of considering the viral epidemic as reversible (vs. irreversible) also plays a role in the socio-representational universe of individuals. Finally, we observe that the attribution of a human origin to the virus is linked to greater collective angst than an attribution to a natural origin. These first results show that it is important to focus on the attribution of the origin of objects of fear in order to understand its consequences in terms of social representations and collective angst.